Faktor-Faktor Promosi Kenaikan Jabatan, Efektifitas Pembagian Tugas dan Keadilan Pembagian Insentif Yang Mempengaruhi Kepuasan Kerja Terhadap Pegawai Dinas Kesehatan Provinsi Jambi Tahun 2016 - Ayu Aztuty Tanjung; Sudiro Sudiro; Sutopo Patria Jati (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2016)
To improve health development in Jambi Province, it needs to be supported by qualified human resource that can improve performance of employees. The decrease in performance might be caused by no work satisfaction among them. One of the problems faced by Health Office of Jambi Province was decreasing a level of work satisfaction among employees from time to time. Promotion, equity in sharing either financial or non-financial incentive, and sharing tasks equally needed to be done in order improve their work satisfaction. The aim of this study was to figure out the influence of promotion, effectiveness in sharing tasks, and equity in sharing incentive towards work satisfaction of employees at the Health Office of Jambi Province. This was an observational study using cross-sectional approach. Number of population was 277 employees of the Health Office of Jambi Province. Meanwhile, number of samples was 74 persons. Data were collected using a questionnaire and analysed quantitatively using methods of univariate, bivariate (a Chi Square test), and multivariate (a Logistic Regression test). The results of this research showed that more than half of the respondents were satisfied (56.8%), had perception of balanced promotion (50%), had good effectiveness in sharing tasks (55.4%), and felt equal in sharing incentive (51.4%). There were any significant relationships between these three variables and work satisfaction of the employees. The results of multivariate analysis demonstrated that variables of promotion (p=0.015) and equity in sharing incentive (p=0.151) jointly influenced work satisfaction of the employees. As suggestions, employees need to pay more attention to the factors of promotion, effectiveness in sharing tasks, and equity in sharing incentive.